Entrepreneurial Thinking in Government Workers Can Make Public Services More Creative and Align with SDGs - Risdayani Risdayani; Yunia Wardi; Susi Evanita; Hendrik Heri Sandi (International Journal Of Economics Social And Technology, 2026)
Public sector organizations are under mounting pressure to abandon rigid, traditional bureaucratic models to address complex global challenges and achieve the Sustainable Development Goals (SDGs). Despite this urgency, current research lacks an integrated framework linking individual entrepreneurial competencies with public sector innovation and sustainability outcomes. This study bridges this gap by exploring the integration of Entrepreneurial Human Capital (EHC) in public organizations. Using a Systematic Literature Review (SLR) based on PRISMA guidelines, this study analyzed 95 peer-reviewed articles exclusively from the ScienceDirect database. Bibliometric mapping via VOSviewer (co-occurrence and overlay analysis) and thematic synthesis were employed to evaluate the literature. The findings reveal a critical novelty: integrating EHC dimensions specifically opportunity recognition, calculated risk-taking, and creativity acts as a catalyst for public sector innovation. Furthermore, the study outlines how these competencies can be operationalized to overcome hierarchical rigidity. Theoretically, this research extends Human Capital Theory by embedding an entrepreneurial dimension into public administration. Practically, it provides a blueprint for policymakers to reform human resource management by institutionalizing EHC to foster adaptive, SDG-aligned public institutions.